Implementation of Multi-sensors to Detect Corona Effects in Medium Voltage Distribution Cubicles - Rahmat, Saepul; Prima Dewi, Riyani; Abdi Musyafiq, Afrizal; Purnata, Hendi (Politeknik Sukabumi, 2022)
Electrical energy is one of the most important energies in everyday life so high-voltage electrical equipment has a vital role in maintaining the reliability of electric power distribution. The corona effect is caused by insulation failure in high-rise equipment which results in disrupted electrical power distribution. The purpose of this research activity is to produce a multi-sensor tool to test the condition of equipment in distribution network booths that have experienced the corona phenomenon. The input data from several sensors used, such as the ozone sensor, will detect ozone gas exposed in the 20kv chamber, detection of ultraviolet light by the UV sensor module, and detection of sound frequency from the hissing of equipment through the microphone sensor experiencing corona will be processed by the Microcontroller and if the value is detected exceeds the reference value that has been set, the output in the form of an LCD will display a corona symptom warning message and instruct the buzzer alarm to sound. The results showed that the prototype of the corona detector was able to identify ozone levels with a maximum value of 21.88 ppb, the largest UV index value of 336, and a maximum hissing frequency of 157 dB in distribution cubicles that experienced the corona effect.